Andras Nursing Informatic System Application (Annisa) dalam Upaya Meningkatkan Pengetahuan Perawat tentang Dokumentasi Keperawatan - Candra Saputra; Yulastri Arif; Fitra Yeni (Jurnal Keperawatan Silampari, 2020)
This study aimed to determine the effectiveness of ANNISA development on nurses' knowledge of nursing documentation. This method uses quantitative research with a quasi-experimental design and a time series approach non-equivocal control group design. The study results were there were differences in the measurement of nurses' knowledge about nursing documentation in the intervention group before the intervention by measuring posttest-1 with p-value = 0.000. There were differences in nurses' experience about nursing documentation between the intervention group and the control group in the posttest-1 and posttest-2 measurements after the intervention using ANNISA with p-value = 0,000. There was an increase in differences in nurses' knowledge about nursing documentation from the pretest, posttest-1, and posttest-2 measurements after using ANNISA in the intervention group and the control group with p-value = 0.000. In conclusion, ANNISA development affects increasing the knowledge of nurses about nursing documentation Keywords: ANNISA, Nursing Documentation, Knowledge